Letter to the editor: Commentary on "Strategic choice in linear sequential unmasking, Roger Koppl, Science & Justice, https://doi.org/10.1016/j.scijus.2018.10.010". Issue 3 (May 2019) - Biedermann, Alex; Gittelson, Simone
Abstract: This letter to the Editor comments on the paper 'Strategic choice in linear sequential unmasking' by Roger Koppl ( Science & Justice, https://doi.org/10.1016/j.scijus.2018.10.010 ).